2008
DOI: 10.1146/annurev.polisci.11.053006.190912
|View full text |Cite
|
Sign up to set email alerts
|

Convenience Voting

Abstract: Forms of convenience voting-early in-person voting, voting by mail, absentee voting, electronic voting, and voting by fax-have become the mode of choice for >30% of Americans in recent elections. Despite this, and although nearly every state in the United States has adopted at least one form of convenience voting, the academic research on these practices is unequally distributed across important questions. A great deal of literature on turnout is counterbalanced by a dearth of research on campaign effects, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 54 publications
3
77
1
4
Order By: Relevance
“…Table 6 shows the effects that contacting has had on turnout over this period. Model 6a the coincidence of increasingly convenient voting methods and higher levels of turnout suggests a possible connection between the two, most research has reported rather modest effects of voting reform (as distinct from registration reform) on turnout levels, from nil (Fitzgerald 2005) to small, usually in a range from 2% to 4% (as summarized by Gronke et al 2008 The comprehensive model of turnout presented in Table 9 confirms the patterns discussed above. The estimated coefficients are all signed as they were in the previous analyses, and those that were significant at conventional levels remained so in the comprehensive model.…”
Section: Datasupporting
confidence: 58%
“…Table 6 shows the effects that contacting has had on turnout over this period. Model 6a the coincidence of increasingly convenient voting methods and higher levels of turnout suggests a possible connection between the two, most research has reported rather modest effects of voting reform (as distinct from registration reform) on turnout levels, from nil (Fitzgerald 2005) to small, usually in a range from 2% to 4% (as summarized by Gronke et al 2008 The comprehensive model of turnout presented in Table 9 confirms the patterns discussed above. The estimated coefficients are all signed as they were in the previous analyses, and those that were significant at conventional levels remained so in the comprehensive model.…”
Section: Datasupporting
confidence: 58%
“…Political scientists refer to these non-polling place forms of voting as convenience voting, of which vote-bymail (VBM) and early in-person voting are the most common (see Gronke et al (2008) for a summary of the literature on convenience voting).…”
mentioning
confidence: 99%
“…The next major communications infrastructure that facilitated remote voting was the telephone network, which has provided an alternative voting procedure for a specific subset of the electorate-usually those with disabilitiesin a small, but significant, number of democratic elections. The telephone network is also used to support convenience voting [22], including voting by FAX. In contrast to the primitive technology used in postal voting, some American astronauts have been able to vote from space since 1997: the first American to do so was David Wolf, who was living on Russia's Mir Space Station and was granted special disposition to vote remotely by his home state of Texas 1 .…”
Section: Introduction: From Post Via Phone To Space and The Cloudmentioning
confidence: 99%